Determinants of meconium-stained amniotic fluid among laboring mother in Ethiopia, systematic review and meta-analysis - Gashaw, Anteneh; Adamu, Yayeh; Sime, Yohanes; Destaw, Belete (Frontiers in Global Women's Health, 2024)
Background Meconium-stained amniotic fluid (MSAF) occurs during childbirth when the amniotic fluid carries traces of meconium, the initial stool passed by a newborn. Often signaling fetal distress, MSAF is linked to heightened risks for both the mother and the newborn. In Ethiopia, there is insufficient attention given to this condition. Despite varied study results indicating a considerable range in MSAF occurrences, there is an absence of a comprehensive national overview. Therefore, this systematic review and meta-analysis aim to evaluate the aggregated prevalence of meconium-stained amniotic fluid among laboring mothers and its influencing factors in Ethiopia, providing a consolidated understanding for healthcare strategies and policies. Method Following PRISMA guidelines, a systematic review and meta-analysis were executed. Extensive literature searches were conducted on PubMed, Google Scholar, and African Online Journal databases. The pooled prevalence was estimated using a weighted inverse variance random effect model. Heterogeneity among studies was evaluated through Cochrane Q-test and I2 statistics. To assess publication bias, a funnel plot and Egger's test were performed. The identification of factors associated with meconium-stained amniotic fluid among laboring mothers in Ethiopia was conducted using Stata v 18 software. Result In total, 63 articles were initially identified, and ultimately, four articles were deemed suitable for inclusion in this review. The combined prevalence of meconium-stained amniotic fluid among laboring mothers in Ethiopia was determined to be 20% (95% CI: 14%–25%). Upon conducting subgroup analysis, it was revealed that the prevalence of meconium-stained amniotic fluid was highest in the Oromia region and lowest in Addis Ababa. Notably, pregnancies complicated by pregnancy-induced hypertension disorder showed a significant association with the presence of meconium-stained amniotic fluid, with an odds ratio of 6.21 (95% CI: 4.04–8.38). Conclusion In conclusion, this review emphasizes the common occurrence of meconium-stained amniotic fluid (MSAF). Notably, it identifies a significant association between pregnancy complicated by hypertension and the presence of MSAF. This underscores the need for targeted interventions to reduce MSAF incidence and mitigate associated adverse outcomes in the Ethiopian. Systematic Review Registration http://www.library.ucsf.edu/, (CRD42023491725).